Genetic variation in lowland sorghum (Sorghum bicolor (L.) Moench) landraces assessed by simple sequence repeats. Issue 2 (26th June 2014) - Amelework, Beyene; Shimelis, Hussien; Tongoona, Pangirayi; Laing, Mark; Mengistu, Fentahun
Abstract : The regions of north-eastern Ethiopia are known for their high levels of sorghum genetic diversity, and for being drought prone. For centuries, sorghum has been developed and maintained by farmers for its adaptation to the marginal and heterogeneous environment of these regions. The objective of this study was to examine the genetic diversity and population structure of 200 sorghum landraces collected from seven lowland districts, using 30 microsatellite markers sampled from all linkage groups of the sorghum genome. Both distance-based and model-based analytical approaches were used to analyse the data. The data analysis revealed that there was a large variation among all the markers under study. The values of polymorphic information content ranged from 0.26 to 0.88, with a mean value of 0.61, reflecting the high discriminating ability of the markers studied. The mean value of total gene diversity was 0.69, which partitioned 86% among the landraces and 14% within the landraces. Gene diversity among the landraces was largely due to the variation among the genotypes within the geographic origins. Landraces sampled from different collection sites appeared to cluster together, indicating the existence of a high level of gene flow among the sites of collection. This indicates that a relatively small, random collection of landraces would capture the bulk of genetic diversity in the target area. A moderately high level of genetic differentiation and a relatively low level of gene flow were observed between sorghum races and maturity groups. Given that the target area is marginal, drought prone and heterogeneous, the study of genetic diversity among sorghum landraces could serve as an important indicator of valuable alleles for drought tolerance in future sorghum improvement programmes.